Akuntansi Wa’d Dalam Akad Pembiayaan Murabahah: (Pendekatan PSAK Syariah No.111) - Eni Latifah (Al-Musthofa: Journal of Sharia Economics, 2020)
This study aims to determine whether there is wa'd accounting in the murabahah financing contract. Wa'd accounting has an impact on financial reports, especially related to murabahah financing in financial institutions, both banking and non-banking. In Wa'd Accounting, there is an alternative accounting treatment for items that are hedged. However, Wa'd accounting has not met the criteria for assets or liabilities so that it is not recognized in the financial statements when giving or receiving wa'd from other parties.